Alpha-Mangosteen lessens high-fat/high-glucose diet and low-dose streptozotocin induced-hepatic manifestations in the insulin resistance rat model - Vivian Soetikno; Prisma Andini; Miskiyah Iskandar; Clark Christensen Matheos; Joshua Alward Herdiman; Iqbal Kevin Kyle; Muhammad Nur Imaduddin Suma; Melva Louisa; Ari Estuningtyas (Taylor & Francis Group, 2023)
AbstractContext α-Mangosteen (α-MG) attenuates insulin resistance (IR). However, it is still unknown whether α-MG could alleviate hepatic manifestations in IR rats.Objective To investigate the effect of α-MG on alleviating hepatic manifestations in IR rats through AMP-activated protein kinase (AMPK) and sterol-regulatory element-binding protein-1 (SREBP-1) pathway.Materials and methods IR was induced by exposing male Sprague-Dawley rats (180-200 g) to high-fat/high-glucose diet and low-dose injection of streptozotocin (HF/HG/STZ), then treated with α-MG at a dose of 100 or 200 mg/kg/day for 8 weeks. At the end of the study (11 weeks), serum and liver were harvested for biochemical analysis, and the activity of AMPK, SREBP-1c, acetyl-CoA carboxylase (ACC), tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, insulin receptor substrate (IRS)-1, Bax and liver histopathology were analyzed.Results α-MG at both doses significantly lowered ALT, AST, triglyceride, and cholesterol total by 16.5, 15.7, 38, and 36%, respectively. These beneficial effects of α-MG are associated with the downregulation of the IR-induced inflammation in the liver. Furthermore, α-MG, at both doses, activated AMPK by 24-29 times and reduced SREBP-1c by 44-50% as well as ACC expression by 19-31% similar to metformin. All treatment groups showed liver histopathology improvement regarding fat deposition in the liver.Conclusions Based on the findings demonstrated, α-MG protected against HF/HG/STZ-induced hepatic manifestations of the IR rats, at least in part via the modulation of the AMPK/SREBP-1c/ACC pathway and it could be a potential drug candidate to prevent IR-induced hepatic manifestations.